SERVICE INNOVATION RISK BASED BUSINESS LICENSING (OSS-RBA) AT THE CAPITAL INVESTMENT AND INTEGRATED ONE STOP SERVICE (DPMPTSP) MAKASSAR CITY - Yanti, Resky; Sakawati, Herlina; Akib, Haedar; Fitri, Anisa (Jurnal Aktor, 2025)
This study aims to find out the innovation of risk-based services (OSS-RBA) in providing quality public services for business actors at the Makassar City Investment and One-Stop Integrated Services Office (DPMPTSP). This research uses a qualitative approach with a descriptive type. So that to achieve the goal, the researcher uses data collection techniques through observation, interviews and documentation. The results of the study show that the innovation of risk-based business licensing services (OSS-RBA) at the Makassar City DPMPTSP has been well implemented and has succeeded in creating quality public services for business actor service users. This refers to the fulfillment of 4 aspects of innovation attributes, namely superior relative advantages compared to the previous licensing system, conformity to the OSS 1.1 licensing system, the possibility of being tried through socialization, technical guidance, online-based services, information service counters and LONTARA programs and ease of observation through increasing the licensing that has been issued and increasing the investment value, while the factors that hinder the implementation of OSS-RBA Innovation are explained in The complexity aspect is technical constraints, the complexity of KPPR, the complexity of KBLI and the level of public knowledge about technology which is still limited and has not been fully resolved